A randomized study of screening for ovarian cancer: a multicenter study in Japan. Issue 3 (1st May 2008) - Kobayashi, H.; Yamada, Y.; Sado, T.; Sakata, M.; Yoshida, S.; Kawaguchi, R.; Kanayama, S.; Shigetomi, H.; Haruta, S.; Tsuji, Y.; Ueda, S.; Kitanaka, T.
Abstract : Ovarian cancer is common in women from developed countries. We designed a prospective randomized controlled trial of ovarian cancer screening to establish an improved strategy for the early detection of cancers. Asymptomatic postmenopausal women were randomly assigned between 1985 and 1999 to either an intervention group ( n = 41, 688) or a control group ( n = 40, 799) in a ratio of 1:1, with follow-up of mean 9.2 years, in Shizuoka district, Japan. The original intention was to offer women in the intervention group annual screens by gynecological examination (sequential pelvic ultrasound [US] and serum CA125 test). Women with abnormal US findings and/or raised CA125 values were referred for surgical investigation by a gynecological oncologist. In December 2002, the code was broken and the Shizuoka Cohort Study of Ovarian Cancer Screening and Shizuoka Cancer Registry were searched to determine both malignant and nonmalignant diagnoses. Twenty-seven cancers were detected in the 41, 688-screened women. Eight more cancers were diagnosed outside the screening program. Detection rates of ovarian cancer were 0.31 per 1000 at the prevalent screen and 0.38–0.74 per 1000 at subsequent screens; they increased with successive screening rounds. Among the 40, 779 control women, 32 women developed ovarian cancer. The proportion of stage I ovarian cancer was higher in the screened group (63%) than in the control group (38%), which did not reach statistical significance ( P = 0.2285). This is to our knowledge the first prospective randomized report of the ovarian cancer screening. The rise in the detection of early-stage ovarian cancer in asymptomatic postmenopausal women is not significant, but future decisions on screening policy should be informed by further follow-up from this trial.